Harry Potter and the deathly hallows - Rowling, J. K. (Rowling, J. K. Harry Potter series, 2007)
Burdened with the dark, dangerous, and seemingly impossible task of locating and destroying Voldemort's remaining Horcruxes, Harry, feeling alone and uncertain about his future, struggles to find the inner strength he needs to follow the path set out before him.